Życie — polityka — władza. Rytuał dnia codziennego ostatniego cara Rosji Mikołaja II w świetle jego dziennika - Garczyk, Bartłomiej (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article concerns the everyday life of Russia emperor Nicholas II, which is seen through the optics of his diary. In the text the plots from the private and official life the last Romanovs tsar — his predilections, occupation, hobby and “state of his soul” are discussed.